Assessing sense of community capacity building in tourism development in Shiraz, Iran - Aref, Fariborz; Redzuan, Ma'rof; Emby, Zahid (Eurojournals, 2009)
The purpose of this paper is to describe a level of sense of community in tourism development for local community in Shiraz. Community capacity building for tourism development requires a range of sense of community. A Sense of community is a necessary condition for tourism development. Specifically, this paper provides an approach for sense of community in relations to tourism development. The paper is based on a study of community capacity building in tourism development which was carried in Shiraz which provides an analysis of the practical application of the approach and implications for community development. The main purpose of the study was to assess the sense of community in tourism development. Lack of community capacity has been identified as barriers to effective tourism development in Shiraz. Thus sense of community was used to measure community capacity building in tourism development. The use of this domain allows community leaders to scrutinize their achievements, address their constraints and measure their progress.